Efikasi salep dari ekstrak daun Turi (Sesbania Grandiflora) sebagai penyembuhan luka bakar terhadap Kelinci (Oryctolagus Cuniculus) - Ulfa Ulfa; Anugrah Umar; Ervianingsih Ervianingsih (Poltekkes Kemenkes Aceh, 2023)
Background: Burns are frequent injuries and can cause serious health problems. Turi leaf extract (Sesbania Grandiflora) has been used as a traditional medicine to treat burns. This study was conducted to determine the effectiveness of ointment from turi leaf extract in healing burns in rabbits.Objectives: This study aimed to evaluate the effectiveness of turi leaf extract cream in rabbits' recovery burnsMethods: The study uses experimental research methods with a single factor design. (single factor design). As for the location of this research, it was carried out in the Pharmaceutical Technology Laboratory of semi-solid preparation, Pharmacy Studies Program of the Faculty of Health Sciences, Muhammadiyah University of Palopo. The study was conducted in the period January-February 2023. The sample used is fresh turia leaves (Sesbania Grandiflora) that are green and cleaned or disorted, then washed with running water until clean. Samples of turi leaves are dried with winding for 3-5 days. The sample is then sprayed with a blender. The data to be analyzed is the percentage of burn healing obtained by measuring the average diameter of the burn. Measurement is done once a day.Results: The results of the study showed that rabbits who were given turia leaf extract ointment had a faster burn healing process compared to the rabbit who was given regular ointments. The area of burns in rabbits given turia leaf extract ointment is also smaller than the rabbit given regular ointments. The ointment from the turia leaf extract is effective in healing burns in rabbits. The results of this study showed that on the 14th day, burns in mice given the FIII dose group (concentration of 7,5%) had the greatest effect on wound healing, followed by the FII dose group (5%) which had a 99,70% healing percentage. The FI dose group had a healing percentage of 85,69%, a positive control of 90,15%, and a negative control of 63,29%.Conclusion: it can be concluded that the ethanol extract of senggani leaves has the potential to heal burns in rats. The FIII dose group that had the highest concentration showed the greatest effect on wound healing. However, the FII dose group with lower concentrations also showed a significant effect in healing burns in rats.